Validity and reliability eines allternativen method for measuring power output during six-second all-out cycling - Watson, M.; Bibbo, D.; Duffy, C. R.; Riches, P. E.; Conforto, S.; Macaluso, A. (Journal of Applied Biomechanics, 2014)
In a laboratory setting where both a mechanically-braked cycling ergometer and a motion analysis (MA) system are available, flywheel angular displacement can be estimated by using MA. The purpose of this investigation was to assess the validity and reliability of a MA method for measuring maximal power output (Pmax) in comparison with a force transducer (FT) method. Eight males and eight females undertook three identical sessions, separated by 4 to 6 days; the first being a familiarization session. Individuals performed three 6-second sprints against 50% of the maximal resistance to complete two pedal revolutions with a 3-minute rest between trials. Power was determined independently using both MA and FT analyses. Validity: MA recorded significantly higher Pmax than FT (P < .05). Bland-Altman plots showed that there was a systematic bias in the difference between the measures of the two systems. This difference increased as power increased. Repeatability: Intraclass correlation coefficients were on average 0.90 ± 0.05 in males and 0.85 ± 0.08 in females. Measuring Pmax by MA, therefore, is as appropriate for use in exercise physiology research as Pmax measured by FT, provided that a bias between these measurements methods is allowed for.